1989
DOI: 10.1111/j.1399-3054.1989.tb05979.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen reserves of leafy spurge (Euphorbia esula) roots as related to overwintering strategy

Abstract: Abstract:Leafy spurge (Euphorbia esula L.), a serious perennial weed of temperature range and pasture lands, has continued to colonize despite various control strategies. The persistence of this species can be attributed in part to the presence of an extensive root system containing abundant organic reserves. These components, established towards the end of the growing season, are remobilized to support early spring growth. Carbohydrates comprise the bulk of reserve material with late fall increments in free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 28 publications
(30 reference statements)
7
45
0
Order By: Relevance
“…The storage proteins usually compose a small part of the total nitrogen pool within the root; their accumulation is related to overwintering. Cyr and Bewley (1989, 1990a, 1990b suggested that, in herbaceous perennial species, some proteins can be used as a temporary nitrogen source to support plant growth when needed.…”
mentioning
confidence: 99%
“…The storage proteins usually compose a small part of the total nitrogen pool within the root; their accumulation is related to overwintering. Cyr and Bewley (1989, 1990a, 1990b suggested that, in herbaceous perennial species, some proteins can be used as a temporary nitrogen source to support plant growth when needed.…”
mentioning
confidence: 99%
“…Vegetative storage proteins have been isolated from various plant organs including soybean pods and leaves (19), potato and yam tubers (7,16), and roots of perennial weeds (4) and from the wood, bark, and leaves of temperate trees (6,8,17,21,24,26). In general, they are not homologous to seed storage proteins of the same species (19).…”
mentioning
confidence: 99%
“…Heaton (1987) and Ehleringer et al (2001) showed the same results, which can be explained by a previous study that linked an increase in δ 15 N values to an increase in humidity (Gremaud and Hilkert, 2009). The problem is that nitrogen is indiscriminant, and nitrogencontaining reserves (amino acids, e.g., arginine, glutamine, and aspartic acid) in xylem could be contributing (Cyr and Bewley, 1989). Because of the perennial growth properties of tea, the early development and growth of buds and leaves is sustained using nitrogen reserves stored in the xylem (Ta et al, 1990;Moing et al, 1994) in different years under different fertilization conditions.…”
Section: N (Vs V-air) Valuesmentioning
confidence: 99%